Reading Projects - Faye Hammill (Forum, 2016)
"By reading only six hours a day", says Marianne Dashwood, outlining her plan of future application to her sister Elinor in Sense and Sensibility, "I shall gain in the course of a twelve-month a great deal of instruction which I now feel myself to want." She adds: "Our own library is too well known to me, to be resorted to for any thing beyond mere amusement. But there are many works well worth reading at the Park; and there are others of more modern production which I know I can borrow of Colonel Brandon" (301). We know, to some extent, what was in the Dashwoods' own library – volumes of Cowper, Scott and Thomson are mentioned. But what might Marianne have borrowed at Barton Park and Delaford? Which publications would Colonel Brandon have considered most appropriate for her project of self-improvement? Elinor considers Marianne's plan excessive, but what would have been a more realistic amount of time for her to spend reading each day, and where might she have done it?